Research trends from 1992 to 2022 of acupuncture anesthesia: a bibliometric analysis - Sun, Linxi; Wei, Xuqiang; Wang, Ke; Zhou, Jia (Frontiers in Medicine, 2023)
Background: Acupuncture anesthesia was a prominent technical development that originated in China in 1958 and was subsequently introduced to the West in the early 1970s. The relative novelty of this technique caused it to become a subject of intense scrutiny and contestation. The use of acupuncture as a complementary treatment for opioid analgesics has been accepted since the early 1970s. Research on acupuncture anesthesia has been beneficial in reducing clinical opioid abuse. Methods: The Web of Science database was searched for publications related to acupuncture anesthesia between 1992 and 2022. The CiteSpace and VOSviewer were used to analyze the annual publications, authors, Co-cited authors, and their countries (regions) and institutions, co-occurrence keywords, burst keywords, Co-citation references and Co-citation journals. Results: A total of 746 eligible publications were retrieved from the database for the analysis, including 637 articles and 109 reviews. And the trend of annual publications continued to grow. Aashish J. Kumar, Daniel I. Sessler, Baoguo Wang, and Paul F. White published the most papers in this field (7), and all authors, had a very low centrality (< 0.01). China (252) and the University of California System (21) were the most productive country (region) and institution, respectively, while the United States (0.62) and University of California System (0.16) had the highest centrality. After removing keywords related to the search strategy, the three most frequent were pain (115), electroacupuncture (109), and stimulation (91). The six most recent burst keywords were recovery, transcutaneous electrical acupoint stimulation, systematic review, quality, general anesthesia, and surgery. Wang, H’s (2014) article had the highest co-citation count (20), whereas Zhang, RX’s (2014) articles had the highest centrality (0.25). The Journal of ANESTHESIA AND ANALGESIA was the most influential one (408 co-citations). Conclusion: This research provides valuable information for the study of acupuncture anesthesia. In recent years, frontier topics in acupuncture anesthesia research have been the promotion of perioperative rehabilitation, anesthesia management, and quality improvement.